Caso de estudio: exportación de saborizante natural a base de aguaje para el mercado chileno - Encalada Augusto, Carlos Enrique (2020)
This paper presents the business proposal for the export of a natural flavoring based on aguaje to the Chilean market. First, we have the current trends in the consumption of products with exotic flavors. Second, we have a constant search for new alternatives for healthy products. Finally, consumer awareness of acquiring natural and nutritious products. The flavoring will be exported through distributors that import natural products with an exotic flavor. The first chapter describes the profile of the country of destination, relevant political, socio-economic, cultural, technological and environmental aspects, as well as consumer analysis and demand projection in Chile. Likewise, the key market dimensions, the market access requirements and the matrix of the competitive profile are detailed. In the second chapter, the commercial strategies for entering the market to achieve the proposed objectives are presented, highlighting the quality of the product, the competitive price, the distribution channel to work, as well as the promotional strategy that is largely linked to the different commercial promotion activities (fairs, business conferences, among others). Therefore, based on the methodologies applied, it is concluded that Chile is an attractive market for the proposed plan that will not only allow to positionate the product, but also to make it more competitive.